Length and diameter of the root canal in deciduous uppers first molars using cone beam computed tomography: an in vitro study - Espinoza Chamorro, Adán Saúl (2016)
Objectives: determine the total length and the largest diameter in cervical, middle and apical level of deciduous mandibular first molars using cone beam computed tomography. Materials and method: In this cross-sectional study a sample of 21 deciduous upper first molars with the length of the complete root and no fracture was analyzed. The teeth were scanned using CT Cone Beam, the diameter of the root canal was measured by taking three points of reference for these measures, cervical, middle and apical. The obtained images were examined and measured by mean a 3D processing imagery software. The measures of the ducts was made by a single observer (CCI= 0.70); nonparametric Kruskal-Wallis test to compare and find the differences were used. Results: The average length of deciduous upper first molars was 13.53 mm, 5.61 mm crown and root 7.92 mm. The average diameter of the palatal root canal was 0.98 mm in cervical level, 0.73 mm in middle level and 0.50 mm in apical level; the average diameter of the mesial root canal was 0.60 mm in cervical level, 0.46 mm in middle level and 0.27 mm in apical level; the average diameter of the distal root canal was 0.70 mm in cervical level, 0.54 mm in middle level and 0.37 mm in apical level. Conclusions: In deciduous first upper molars the diameters of the palatal root canal were the largest diameter in all levels. The mesial of the first molars is the root that presents the shortest diameter at his roots canals in all levels (cervical, middle and apical).